2019
DOI: 10.5267/j.ac.2019.4.001
|View full text |Cite
|
Sign up to set email alerts
|

An explanatory review of audit market concentration and auditor workload in Malaysia

Abstract: The purpose of this study is to provide updated information and facts about the Malaysian audit market concentration and auditor workload. The global auditing services market is presently dominated by a group of four audit firms which known as Big 4; namely Deloitte, PriceWaterhouseCoopers, Ernst & Young and KPMG. The audit industry in Malaysia offers several exemptions, as observed that two of non-big 4 audit firms succeeded to make their place into the Malaysian top 4. The study examined the audit firms shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The key challenge faced by the profession in Malaysia is many practitioners have difficulties in complying with increasingly complex audit performance standards coupled with high staff turnover due to high demand from non-public accounting sectors [Malaysian Institute of Accountants (MIA), 2018]. This shortage of manpower has led to high workload for existing auditors (Raza et al , 2019). A joint study by the Association of Chartered Certified Accountants (ACCA) and AOB in 2013 found that many auditors in Malaysia want improvement where remuneration and WLB are concerned.…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…The key challenge faced by the profession in Malaysia is many practitioners have difficulties in complying with increasingly complex audit performance standards coupled with high staff turnover due to high demand from non-public accounting sectors [Malaysian Institute of Accountants (MIA), 2018]. This shortage of manpower has led to high workload for existing auditors (Raza et al , 2019). A joint study by the Association of Chartered Certified Accountants (ACCA) and AOB in 2013 found that many auditors in Malaysia want improvement where remuneration and WLB are concerned.…”
Section: Background and Prior Researchmentioning
confidence: 99%